2017
DOI: 10.1002/aqc.2840
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population history ofTanichthys albonubes(Teleostei: Cyprinidae): Implications for conservation

Abstract: Tanichthys albonubes is a cyprinid fish of South China and North Vietnam. Although this species has been sold worldwide in the aquarium trade for more than a century, it is listed as a second‐class state‐protected animal in China and classified as ‘extinct in nature’ in the China Red Data Book. To investigate the population history of T. albonubes and evaluate the genetic conditions among the wild and hatchery populations, mitochondrial genes (mtDNA, 2032 bp from the d‐loop and cyt b), nuclear genes (nuDNA, 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 78 publications
(114 reference statements)
3
13
1
Order By: Relevance
“…Previous data may have been obtained by an inaccurate counting method. The sampling locality of the lineage "DX" (from Dongxing City, Guangxi Province) in Zhao et al (2018) and Li et al (2020), which is the same as the type locality of T. albiventris (coded JP in the present study), was provided by the first author of this study via Dr. Hung-Du Lin who was the corresponding author of Zhao et al (2018). Li et al (2020) reported eight branched anal-fin rays for this population based on the examination of 30 specimens, whereas in the present study, the number of branched anal-fin rays of the JP population is 9-10 (mostly 9), and that of the HZ population of T. albiventris from an adjacent basin is 9-11 (mostly 9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous data may have been obtained by an inaccurate counting method. The sampling locality of the lineage "DX" (from Dongxing City, Guangxi Province) in Zhao et al (2018) and Li et al (2020), which is the same as the type locality of T. albiventris (coded JP in the present study), was provided by the first author of this study via Dr. Hung-Du Lin who was the corresponding author of Zhao et al (2018). Li et al (2020) reported eight branched anal-fin rays for this population based on the examination of 30 specimens, whereas in the present study, the number of branched anal-fin rays of the JP population is 9-10 (mostly 9), and that of the HZ population of T. albiventris from an adjacent basin is 9-11 (mostly 9).…”
Section: Discussionmentioning
confidence: 99%
“…Tanichthys comprises four species, including Tanichthys albonubes Lin, 1932 (white cloud mountain minnow), Tanichthys kuehnei Bohlen, Dvořák, Thang & Šlechtová, 2019, Tanichthys micagemmae Freyhof & Herder, 2001, and Tanichthys thacbaensis Nguyen & Ngô, 2001. Unlike the other three species restricted to specific river basins with a narrow geographic distribution in northern and central Vietnam, T. albonubes has a wide distribution ranging across several different basins (the River Pearl and several small coastal rivers) in southern China (including Guangdong, Guangxi, Hainan and Hong Kong) and northern Vietnam (Quang Ninh Province) (Weitzman & Chan 1966, Pan 1991, Chen 1998, Kottelat 2001, Yi et al 2004, Chan & Chen 2009, Li & Li 2011, Zhao et al 2018. Recent molecular studies indicated that each of the wild populations of T. albonubes was monophyletic with significant genetic differentiation among them (Luo et al 2015, Zhao et al 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, our study examined the population genetic structure and diversity of N. bathybius in the northern South China Sea using the genetic variability of the mitochondrial DNA (mtDNA) cytochrome b gene (cyt b), with the aim of revealing its demography. The sequences of mtDNA cyt b are usually used to reconstruct demographic history and animal phylogeography (e.g., Garra orientalis [31], Tanichthys albonubes [32], Neocaridina [33], Scatophagus argus [34], Capra pyrenacia pyrenacia [35]).…”
Section: Introductionmentioning
confidence: 99%
“…T. albonubes was first discovered on White Cloud Mountain in Guangzhou City, Guangdong Province, South China (Lin, 1932), and was thought to be monotypic and endemic to the Pearl River Delta region (Chen, 1998). Since the 21st century, wild populations of T. albonubes have been continuously discovered in many sites, including Guangzhou, Huizhou, Luhe and Qingyuan in Guangdong Province (Chen, 2010; Yi et al ., 2004; Zhao et al ., 2018), Guiping (Li & Li, 2011) and Dongxing in Guangxi Province, Hainan Island (Chan & Chen, 2009) and north‐east Vietnam (Kottelat, 2001). Among these newly discovered populations, the population of Qingyuan was confirmed to have originated from hatchery release (Zhao et al ., 2018; Li et al ., 2020b) and hence the original Qingyuan population described by Zheng (1989) may have become extinct.…”
Section: Introductionmentioning
confidence: 99%